Diagnostic Accuracy of Strain Elastography Ultrasound in Differentiation of Benign and Malignant Breast Lesions with Histopathological Correlation - Yasmin, Tarana; Amin, Mashah Binte; Sarkar, Samar Chandra; Kabir, Kaniza; Faria, Samanta (Journal of Enam Medical College, 2021)
Background: Palpable breast masses are common and usually benign, but efficient evaluation and prompt diagnosis are necessary to rule out malignancy. High frequency high resolution ultrasonogram helps in its evaluation. With major advances in ultrasonographic technology, ultrasound elastography can improve differentiation between benign and malignant breast lumps. Knowledge of the specific ultrasonogram elastographic characteristics of breast lumps can be offered as a viable alteration to biopsy and imperative for optimal patient management. Objective: To determine the validity of ultrasound elastography strain ratio in differentiation of benign and malignant breast lesions by detecting the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of ultrasound elastography in diagnosis of benign and malignant breast lesions. Materials and Methods: This cross-sectional analytical study was done in the department of Radiology & Imaging of Enam Medical College & Hospital during July 2016 to June 2017. A total number of 104 patients were included in this study. Data on clinical presentation, ultrasonographic, sonoelastographic findings including histopathological report were collected and documented in structured forms. Analysis was done using SPSS 20.0 version. Results: The study was done on 104 women of 19−60 years of age with the mean age of 34.65±5.5 years. Out of sonographically diagnosed 80 benign lesions also having lower elastography strain ratio (2.73±0.87), 75 (94%) were proved benign histopathalogically. With these criteria for diagnosis of benign lesion, sensitivity was 94.9%, specificity 80%, positive predictive value 93.7%, negative predictive value 83.3% and accuracy 91.3%. Sonographically 24 lesions were diagnosed as malignant also having higher elastography strain ratio (8.1±1.38), out of these 20 (83%) cases were proven malignant histopathalogically with sensitivity of 80%, specificity 94.9%, positive predictive value 83.3%, negative predictive value 93.7% and accuracy 91.3%. Conclusion: Ultrasound elastographic findings of benign and malignant breast lesions correlated well in most of the cases with the histopathological results. So combined use of ultrasound and ultrasound elastography provide better diagnostic yield and thus allowed sparing of cumbersome invasive diagnostic procedures. J Enam Med Col 2021; 11(2): 99-107